The trend of business intelligence adoption and maturity - Qushem, Umar; Abubakar Ibrahim, Adamu; Zeki, Akram M.; Akleylek, Sedat (IEEE, 2017)
In this paper, the trend of Business Intelligence (BI) adoption and maturity has been evaluated. Special emphasis was given to the small-to-medium enterprises (SME) business adoption and intensive review of BI maturity model in for the contemporary business world. Therefore, this study surveyed research works that reveal most determinants for BI efficiency. The survey has extract what lead organization to a better understanding of development and testing of BI framework. The study has found out that BI adoption has been highly related to Information and Communication Technology (ICT) tool utilization. Moreover, the success of BI to business are observed when users are able to leverage the best use of their data, by summarizing and aggregating information for business goals. Thus, understanding the fact, an investigation has been approached to identify BI adoption trends towards companies using BI. Results revealed that technology company, as well as a Production company, took the highest in BI adoption.